Pemphigoid diseases in patients with end-stage kidney diseases: pathogenesis and treatment - Yang, Liu-Yi-Yi; Wang, Yu-Lu; Zuo, Ya-Gang (Frontiers in Immunology, 2024)
Background Pemphigoid diseases constitute a group of autoimmune blistering disorders characterized by subepithelial blistering. The association between pemphigoid diseases and both end-stage kidney disease (ESKD) and its treatment is notable. However, there is limited evidence about the management of pemphigoid diseases in patients with ESKD. This systematic review compiled case reports and relevant studies, summarized the underlying mechanisms of pemphigoid diseases in patients with ESKD, and summarized the efficacy of various therapies. Methods A systematic search of PubMed and Embase was performed for articles published between 1982 to June 2, 2024. Results Fifty-three case reports and eight relevant studies were included. Triggers for pemphigoids in patients with ESKD included materials used to treat ESKD, immune dysregulation of patients with ESKD, and rejection of renal allograft. Treatment for these patients included removing triggers, as well as administering of corticosteroids, mycophenolate mofetil (MMF), tetracyclines, rituximab, methotrexate, dapsone, azathioprine, cyclosporine, intravenous immunoglobin (IVIG), plasmapheresis, and Janus kinase inhibitors. Conclusion Removing triggers is the most effective strategy. Despite their suboptimal efficacy, corticosteroids remain the most commonly used agents in this patient population. MMF, tetracyclines, and rituximab are less used but with benefits. There are significant adverse effects associated with methotrexate treatment. Other treatment may also be beneficial and require further investigation. These findings may enable clinicians to optimize the therapeutic approach for these patients.